Factors influencing participation in colorectal cancer screening among average-risk populations: A descriptive-analytical study in a developing country - Farimah Rahimi; Reza Rezayatmand; Zahra Dalvand; Zahra Ravankhah; Peyman Adibi (PLoS ONE, 2025)
Introduction Colorectal cancer (CRC) is a leading cause of cancer-related deaths globally, with early detection significantly improving treatment outcomes. Understanding the factors influencing the decision to participate in colorectal cancer screening programs can help design interventions to improve these programs. Method This study investigates factors influencing CRC screening participation among average-risk individuals aged 50–70 years in Isfahan province, utilizing data from the comprehensive E-health information system. Employing Andersen’s Behavioral Model, the study examines predisposing, enabling, and need-for-care factors. A logistic regression model was used to identify significant predictors of screening participation. Results The analysis in this study includes 808,978 average-risk individuals in Isfahan, with a mean age of 56.67 years (SD = 7.17). Results indicate that younger age, male gender, marital status, health insurance coverage, flexible work time pattern, Iranian nationality, and high-risk lifestyles positively influence the probability of participation. The predictor screening analysis reveals that lifestyle, chronic disease, and education are the top three factors influencing participation, with lifestyle being the most dominant predictor. Conclusion Participation in colorectal cancer screening is influenced by numerous factors. Therefore, it is recommended that all important factors determining individuals’ participation in colorectal cancer diagnosis be considered and that individuals’ lifestyles be adjusted to encourage effective participation in colorectal cancer screening. Understanding these factors can guide targeted interventions to enhance CRC screening uptake and early detection.